Victorian Shadows and Southern Echoes: A Simultaneous Scrutiny of Social Class Disparity in ‘Oliver Twist’ and ‘To Kill a Mockingbird’ - Md. Mehedi Hassan (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa)
This study examines social class discrimination in Harper Lee’s To Kill a Mockingbird and Charles Dickens’s Oliver Twist, focusing on their similarities and differences in addressing this issue across distinct historical contexts—Victorian England and 1930s Alabama. Utilizing qualitative methods, the study explores how protagonists Oliver Twist and Scout Finch navigate oppressive social hierarchies and systemic injustices within their societies. Both novels tackle themes of poverty, morality, and the impact of socio-economic status on individuals’ lives, illuminating the inherent inequalities of their respective worlds. Dickens portrays the brutal realities faced by the lower classes through depictions of the criminal underworld, orphanages, and workhouses, while Lee focuses on racial prejudice and the quest for justice during the Great Depression. Employing Marxist theory, this analysis critically reveals how class conflicts and socio-economic disparities inform the narratives, underscoring social injustices and the hypocrisy surrounding them. Though both authors address the plight of marginalized groups, they emphasize different aspects: Lee highlights racial injustice and ethical growth, while Dickens critiques the systemic exploitation of the poor. Ultimately, this comparative study enhances our understanding of societal inequality as presented in literature, deepening our awareness of race, morality, and class dynamics in both novels.